Dimensional Stability and Wettability of Modified Samama (Anthocephallus macrophyllus) Wood with Boron, Citric Acid, and Heat Treatment - Priadi, Trisna; Wardhani, Miranti Kusuma; Putra, Guruh Sukarno; Cahyono, Tekat Dwi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
This research aimed to address the leaching phenomenon of boron preservatives in wood. The subsequent investigation focuses on wood's dimensional stabilization and wettability after a two-stage impregnation process. Samama (Anthocephallus macrophyllus) wood was impregnated with boron (boric acid, borax, and a combination of both) at a pressure of 7 atm for 4 hours, with each preservative’s concentration set at 5%. After oven drying at 60°C until achieving a 15% moisture content, the next step involves a second-stage impregnation with citric acid (at a 5% concentration) under the same pressure and duration. The final step included heat treatment at 80°C and 160°C for 4 hours. The research results indicate that boron and citric acid enhance the dimensional stabilization of samama wood. The best dimensional stabilization treatment combines boric acid, borax, citric acid, and heat treatment at 160°C. This study confirms that citric acid improves the dimensional stabilization of samama wood, whether used with boron or not. Compared to treatments without citric acid and heating, the two-stage impregnation reduces boron leaching by up to 30%. The research also recommends that all treatments exhibit good finishing properties. Keywords: Anthocephallus macrophyllus, boron, dimension stabilization, impregnation, wettability